1955
DOI: 10.1210/endo-56-3-225
|View full text |Cite
|
Sign up to set email alerts
|

FURTHER STUDIES ON THE NEUROGENIC CONTROL OF THE ESTROUS CYCLE BY UTERINE DISTENTION1

Abstract: T HE mechanism by which the corpus luteum is caused to persist following fertilization in mammals which ovulate spontaneously during each reproductive cycle and which do not show pseudopregnancy following cervical stimulation is not known. The effects of uterine distention and the apparent importance of the" uterine afferent nerve supply on the regulation of the estrous cycle of the ewe have been observed by Moore and Nalbandov (1953). They have shown that a foreign body introduced into the sheep uterus during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1957
1957
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…In view of the present failure to significantly reduce the cycle length with two beads in one horn this result is a little surprising, but the presence of a thread passing through the endometrium may account for this discrepancy. Nalbandov, Moore & Norton (1955) found that there was little change in the degree of shortening of the oestrous cycle of the sheep when 4 mm plastic beads were substituted for the 8 mm size. With 4 mm beads the shortening effect was mainly restricted to the current cycle while with the larger size the cycles were curtailed as long as the bead remained in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the present failure to significantly reduce the cycle length with two beads in one horn this result is a little surprising, but the presence of a thread passing through the endometrium may account for this discrepancy. Nalbandov, Moore & Norton (1955) found that there was little change in the degree of shortening of the oestrous cycle of the sheep when 4 mm plastic beads were substituted for the 8 mm size. With 4 mm beads the shortening effect was mainly restricted to the current cycle while with the larger size the cycles were curtailed as long as the bead remained in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the cycle is shortened or prolonged depends on the stage of the cycle when the bead is placed in the uterus and on the size of the bead. That the nervous system is involved is demonstrated by the fact that when the uterine segment containing the bead is denervated there is no effect on the oestrous cycle (Inskeep, Oloufa, Howland, Pope & Casida, 1962;Moore & Nalbandov, 1953;Nalbandov, Moore & Norton, 1955).…”
Section: Introductionmentioning
confidence: 99%
“…Moore and Nalbandov (1953), Nalbandov, Moore, and Norton (1955), and Inskeep et al (1962) noted a similar shortening in the length of the oestrous cycle in ewes with plastic beads sutured to the uterus. This effect appears to be due to a neural-mediated influence between days 3 and 8 of the oestrous cycle.…”
Section: Discussionmentioning
confidence: 82%
“…In the ewe, as in other species, the presence of an intra-uterine foreign body interferes with the physiological function of the organ and causes infertility. Intra-uterine foreign bodies in the ewe have been shown to interfere with the development of the corpus luteum (Ginther, Pope, and Casida, 1965;Stormshak, Lehmann, and Hawk 1967), to modify uterine motility (Brinsfield and Hawk 1969), to inhibit sperm transport and promote spermicidal conditions (Hawk 1967), and in certain circumstances to modify cycle length (Moore and Nalbandov 1953;Nalbandov, Moore, and Norton 1955;Inskeep et al 1962). Therefore, there would seem good reason to suggest that in the cannulated uterus, the volume of fluid collected may be influenced by local effects of the cannula on the uterus.…”
Section: Discussionmentioning
confidence: 99%